EXPLORING THE IMPACT OF PECHAKUCHA PRESENTATIONS IN THE EFL CLASSROOM - Tsai, Kuei-Ju (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Oral presentation skills are widely accepted as key to academic and professional success. Despite the general consensus, in Taiwan very little has been done to develop students’ oral presentation skills in school curriculum throughout formal education. It is not uncommon to see Taiwanese undergraduates give unsatisfactory oral presentations; the plight is even worse if done in English. The reasons for such poor presentation performance may be partly attributed to students’ lower English speaking proficiency, but also due to the lack of proper training. This paper reports on a study looking into the effects of overt instruction of oral presentation skills on Taiwanese EFL undergraduate students’ 1) English presentation performance and 2) overall English speaking proficiency. In the study, two groups of students (N=42) received the same overt instruction of oral presentation skills (guided by the principles by van Ginkel, 2015), but they were required to present with varying formats. The treatment group presented with the PechaKucha format (20 slides*20 seconds), while the control group was only given a general time limit (400 seconds). Measurements were taken before and after the pedagogical intervention, including a pre-treatment presentation and a speaking pretest, a post-treatment presentation and a speaking post-test. In general, findings showed that the overt instruction did enhance students’ overall presentation performance, regardless of the format. While the two groups did not differ significantly on overall presentation performance, they exhibited differences in certain criteria including content, organization, and body language. The PechaKucha group outperformed their counterpart on the organization of their speech, but scored significantly lower on the content information. A closer look into the presentations of the PK group revealed that some students may have resorted to a circumvention strategy to work around the PechaKucha constraints on the number of slides and time limit.